2021
DOI: 10.3389/fenvc.2021.771759
|View full text |Cite
|
Sign up to set email alerts
|

Sr Isotopic Composition of NIES Certified Reference Material No. 28 Urban Aerosols

Abstract: An interlaboratory study of the National Institute for Environmental Studies (NIES) certified reference material (CRM) No. 28 Urban Aerosols collected from the filters of a central ventilating system in a building in the Beijing city center from 1996 to 2005 was performed to obtain an information value of the Sr isotopic composition. The Sr isotopic composition was measured using multi-collector-inductively coupled plasma-mass spectrometry (MC-ICP-MS) to confirm the CRM’s within- and between-bottle homogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…For PACS-3, δ 65/63 Cu and δ 66/64 Zn were consistent with those reported by Jeong et al 16 within 0.1‰, and 206 Pb/ 207 Pb was consistent with that reported by Jeong et al 16 within 2‰. For NIES-28, δ 66/64 Zn was the same as that reported by Liao et al, 19 and the isotope ratios of Pb were consistent with those reported by Yamakawa et al 20 within 2‰. The n indicates the number of fractions divided from one digested reference material.…”
Section: Interferences Of Coexistingsupporting
confidence: 89%
“…For PACS-3, δ 65/63 Cu and δ 66/64 Zn were consistent with those reported by Jeong et al 16 within 0.1‰, and 206 Pb/ 207 Pb was consistent with that reported by Jeong et al 16 within 2‰. For NIES-28, δ 66/64 Zn was the same as that reported by Liao et al, 19 and the isotope ratios of Pb were consistent with those reported by Yamakawa et al 20 within 2‰. The n indicates the number of fractions divided from one digested reference material.…”
Section: Interferences Of Coexistingsupporting
confidence: 89%